Correction of malocclusion in individuals with osteogenesis imperfecta: a systematic review (Research, Society and Development, 2022)
The aim of the study was to verify the viability of the correction of malocclusion in individuals with osteogenesis imperfecta (OI). A systematic review was developed using PubMed, Web of Science, Scopus, Lilacs, Ovid, Google Scholar and OpenGrey databases. The review was registered in PROSPERO (CRD42018114217). Data extraction was conducted by two researchers. Studies describing orthodontic treatment, orthognathic surgery or orthodontic treatment combined with orthognathic surgery for the correction of malocclusion in individuals with OI were eligible. The methodological quality of the articles was appraised using the case report assessment tool proposed by the Joanna Briggs Institute. The results were synthesized qualitatively. The 22 case reports included in the present review involved a total of 28 clinical cases. Malocclusion was considered severe in 11 cases, with records of negative overjet between nine and 26mm. Orthodontic treatment was performed in four cases, orthognathic surgery was performed in five cases and orthodontic treatment combined with orthognathic surgery was performed in 19 cases. All treated cases had favorable clinical results. Overall, the methodological quality of the articles included was satisfactory. Based on the analyzed cases, which reported only cases with successful results, treatment for malocclusion is viable in individuals with OI. When duly indicated, treatment can be performed with orthodontic treatment, orthognathic surgery or a combination of both, providing satisfactory esthetic and functional results with adequate stability.